Enhanced Arboviral Surveillance to Increase Detection of Jamestown Canyon Virus Infections, Wisconsin, 2011-2016 - Matkovic, Eduard; Hoang Johnson, Diep K; Staples, J Erin; Mora-Pinzon, Maria C; Elbadawi, Lina I; Osborn, Rebecca A; Warshauer, David M; Wegner, Mark V; Davis, Jeffrey P (The American journal of tropical medicine and hygiene, 2019)
Jamestown Canyon virus (JCV), a mosquito-borne (within the California serogroup), can cause severe neuroinvasive disease. According to national data during 2000-2013, 42% of the 31 documented JCV disease cases in the United States were detected in residents from Wisconsin. The Wisconsin Division of Public Health enhanced JCV surveillance by implementing routine use of JCV-specific immunoglobulin M (IgM) antibody testing followed by confirmatory JCV-specific plaque reduction neutralization testing on all patients with suspected cases of arboviral infection who had tests positive for arboviral immunoglobin at commercial laboratories. During 2011-2016, of the 287 Wisconsin specimens tested on the Arbovirus IgM Antibody Panel, 30 JCV cases were identified (26 confirmed and four probable). Twenty-seven (90%) JCV cases were detected after 2013. Among all cases, 17 (56%) were male and the median age was 54 years (range: 10-84 years). Fifteen patients had neuroinvasive disease, including meningitis ( = 9) and meningoencephalitis ( = 6). Although historically considered rare, the relatively high rate (0.12 cases/100,000 population) of diagnosis of JCV infections among Wisconsin residents during 2013-2016 compared with that in previous years suggests occurrence is widespread throughout Wisconsin and historically may have been under-recognized. This study aims to raise awareness of JCV infection for differential diagnosis among the arboviral diseases. Improved and timely diagnosis of arboviral disease is important in that it will provide more information regarding emerging infections and promote preventive measures to avoid mosquito-borne exposure and infection among residents of and visitors to affected areas.